NT5C2 methylation regulatory interplay between DNMT1 and insulin receptor in type 2 diabetes - Chen, Yng-Tay (Sci Rep, 2020)
Epigenetics alternation of non-genetic variation and genome-wide association study proven allelic variants may associate with insulin secretion in type 2 diabetes (T2D) development. We analyzed promoter DNA methylation array to evaluate the associated with increased susceptibility to T2D (30 cases, 10 controls) and found 1,091 gene hypermethylated in promoter regions. We performed the association study of T2D and found 698 single nucleotide polymorphisms in exon and promoter sites by using 2,270 subjects (560 cases, 1,710 controls). A comparison of DNA hypermethylation and gene silencing of mouse T2D results in our T2D patients’ results showed that the 5′-nucleotidase, cytosolic II (NT5C2) and fucosyltransferase 8 (FUT8) genes were strongly associated with increased susceptibility to T2D. DNA hypermethylation in promoter regions reduced NT5C2 gene expression, but not FUT8 in T2D patients. NT5C2 protein expression was decreased in pancreatic β-cells from T2D mice. Transient transfection NT5C2 into RIN-m5F cells down-regulated DNA methyltransferase I (DNMT1) expression and up-regulation of the insulin receptor. Moreover, NT5C2 knockdown induced in DNMT1 overexpression and insulin receptor inhibition. Taken together, these results showed that NT5C2 epigenetically regulated insulin receptor in patients and mice with T2D, and maybe provide for T2D therapy strategy.